Global policy transfer for land administration and disaster risk management. (December 2020) - Unger, Eva-Maria; Bennett, Rohan; Lemmen, Christiaan; de Zeeuw, Kees; Zevenbergen, Jaap; Teo, CheeHai; Crompvoets, Joep
Highlights: Global policy development is increasingly shaped through the SDGs. UN-GGIM plays a leading role in the development of policy frameworks for geospatial information. Two frameworks tackle global issues in relation to tenure security and natural disasters. Policy transfer is required to occur between governance layers and functional areas. Opportunity to utilize a networked approach for a robust and further-reaching uptake of policies. Abstract: Contemporary global policy development is increasingly shaped through the Sustainable Development Goals (SDGs). In parallel, the United Nations initiative on Global Geospatial Information Management (UN-GGIM) plays a leading role in the development and diffusion of policy frameworks with regard to geospatial information. Specifically, two frameworks, the Framework for Effective Land Administration (FELA) and the Strategic Framework for Geoinformation Services for Disaster (SFGISD), are under development to tackle global issues in relation to tenure security and natural disasters. In order to harmoniously diffuse those global goals and frameworks into national laws and regulations, and to local community initiatives and policies, policy transfer is required to occur between governance layers. This paper seeks to assess 'whether' and 'how' this policy transfer occurs, focusing specifically on identifying limitations and its opportunities for its enhancement. Results reveal that the approach so far used for policy transfer is taking conventional institutional means to do this in both domains land administration and disaster risk management (DRM) domains. There appears to be an opportunity to utilize a networked approach instead of the conventional institutional for a more robust and further-reaching uptake of the policies. This could also give space to provide better mechanisms for feeding results from local level initiatives and successes into the global frameworks.